2022
DOI: 10.1038/s41598-021-04544-6
|View full text |Cite
|
Sign up to set email alerts
|

A specific hybridisation internalisation probe (SHIP) enables precise live-cell and super-resolution imaging of internalized cargo

Abstract: Facilitated by the advancements in microscopy, our understanding of the complexity of intracellular vesicle traffic has dramatically increased in recent years. However, distinguishing between plasma membrane-bound or internalised ligands remains a major challenge for the studies of cargo sorting to endosomal compartments, especially in small and round cells such as lymphocytes. The specific hybridization internalisation probe (SHIP) assay, developed for flow cytometry studies, employs a ssDNA fluorescence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…We also detected a trend of increase membrane enrichment at 15 min after activation as compared to the resting state but this was not statistically significant. We followed the localisation of Vti1b in more detail and observed that Vti1b was found at the BCR-enriched plasma membrane areas and at sites of antigen-BCR internalisation or internalized antigen vesicles, both visible as clusters close to the plasma membrane ( Hernández-Pérez and Mattila, 2022 ) already at 5 min after activation ( Figure 2A , arrows; Figure 2C ). Colocalisation of Vti1b with the antigen was also observed at 15 and 30 min, both close to the plasma membrane and in vesicles inside the cell.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also detected a trend of increase membrane enrichment at 15 min after activation as compared to the resting state but this was not statistically significant. We followed the localisation of Vti1b in more detail and observed that Vti1b was found at the BCR-enriched plasma membrane areas and at sites of antigen-BCR internalisation or internalized antigen vesicles, both visible as clusters close to the plasma membrane ( Hernández-Pérez and Mattila, 2022 ) already at 5 min after activation ( Figure 2A , arrows; Figure 2C ). Colocalisation of Vti1b with the antigen was also observed at 15 and 30 min, both close to the plasma membrane and in vesicles inside the cell.…”
Section: Resultsmentioning
confidence: 99%
“…Then, cells were fixed with 4% PFA for 10 min at RT, washed, mounted using FluoroMount-G containing DAPI, and imaged as described above. For live cell imaging, samples were prepared and imaged as described in Hernández-Pérez and Mattila, 2022 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, however, the colocalization of Rab9 and CatS was at lower levels in resting cells and clearly triggered by antigen activation, further suggesting the overlapping yet separate functions of Rab7 and Rab9 in relation to antigen processing. However, due to the small cytoplasmic space and vesicle size in B cells, the resolution of light microscopy often becomes limiting and colocalization analysis should also be interpreted with caution [54]. Testing the idea of whether vesicular compartments, or vesicle domains, with differential Rab7 or Rab9 could also behave differently in antigen degradation, we labeled antigen with DQ-Ova, which generates the fluorescent signal only upon degradation, and indeed found a significantly brighter fluorescence in Rab7 + endosomes compared to Rab9 + counterparts (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Samples were then washed with cold PBS and analyzed. The internalization rate for the biotinylated anti-IgM samples was calculated as described previously ( Hernández-Pérez and Mattila, 2022 ). A BD LSR Fortessa analyser equipped with four lasers (405, 488, 561, and 640 nm) was used.…”
Section: Methodsmentioning
confidence: 99%